2014
DOI: 10.2136/vzj2014.02.0014
|View full text |Cite
|
Sign up to set email alerts
|

Heated Fiber Optic Distributed Temperature Sensing: A Dual‐Probe Heat‐Pulse Approach

Abstract: Implementation of the dual-probe heat-pulse (DPHP) approach for measurement of volumetric heat capacity (C) and water content (q) with distributed temperature sensing heated iber optic (FO) systems presents an unprecedented opportunity for environmental monitoring (e.g., simultaneous measurement at thousands of points). We applied uniform heat pulses along a FO cable and monitored the thermal response at adjacent cables. We tested the DPHP method in the laboratory using multiple FO cables at a range of spacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…Unfortunately, due to the construction of DTS cables, the contact and thermal resistance between the armored fiber‐optic cable and surrounding soil can be worse than that for SPHP. The DPHP approach has also been applied to an AHFO‐DTS system (Benítez‐Buelga et al, ). However, as stated above, the DPHP is very sensitive to the spacing ( r ) between the heat and sensor probes, and keeping two long cables (1 m to 10 km) parallel at an exact fixed distance can be problematic for the AHFO‐DTS.…”
Section: Application Of the Hp Methods In Unfrozen And Frozen Soilsmentioning
confidence: 99%
“…Unfortunately, due to the construction of DTS cables, the contact and thermal resistance between the armored fiber‐optic cable and surrounding soil can be worse than that for SPHP. The DPHP approach has also been applied to an AHFO‐DTS system (Benítez‐Buelga et al, ). However, as stated above, the DPHP is very sensitive to the spacing ( r ) between the heat and sensor probes, and keeping two long cables (1 m to 10 km) parallel at an exact fixed distance can be problematic for the AHFO‐DTS.…”
Section: Application Of the Hp Methods In Unfrozen And Frozen Soilsmentioning
confidence: 99%
“…Several minutes or hours of alternate or direct current voltage are needed to produce this heating, and the electric cable is typically integrated into the same fibre cable. The use of a separate electrical cable kept at a constant distance from the optical fibre was investigated with interesting results [123][124][125]. Nonetheless, it is required that the optical fibre and the electrical cable be separated by a constant distance all along the cable-a condition not so easy to achieve in practical applications.…”
Section: Distributed Temperature Sensing For Soil Levees and Embankmentsmentioning
confidence: 99%
“…The mechanism is similar to that exploited for leakage detection: different levels of soil moisture lead to different thermal conductivity, and in turn to a differential temperature behaviour for heating and cooling cycles (Figure 8b) or for seasonal temperature variations. In particular, it was shown that the accuracy of the active method [120,123,129] was sufficient to qualitatively assess the local degree of saturation and the volumetric heat capacity. Nonetheless, optical fibre sensing systems provide lesser accuracy than traditional probes, such as dielectric acquameters or electrical time domain reflectometers: for this reason, Sayde et al [130] proposed to integrate the temperature deviation over time.…”
Section: Distributed Temperature Sensing For Soil Levees and Embankmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHFO‐DTS is similar to the SPHP in theory, but uses a fiber‐optic cable to measure soil temperature and thus could potentially extend the temperature, thermal properties, and θ measurement scales from a point to an intermediate landscape scale. A DPHP‐based AHFO‐DTS system was also tested to measure C and θ by installing two or more fiber‐optic cables paralleling each other, which has the same drawbacks as the DPHP (Benítez‐Buelga et al, 2014). To further develop an SPHP‐based AHFO‐DTS, there is a need to extend the measurements from λ to C and θ for the SPHP.…”
mentioning
confidence: 99%